Flexible fiber-based organic phototransistor serum amyloid protein A sensor and preparation method thereof
Through the design and preparation of flexible fiber-based organic phototransistors, the existing serum amyloid A sensor has solved the problem of complex operation and long detection time, and achieved rapid, sensitive and dedicated serum amyloid A detection, which is suitable for use in Wear biosensors.
Patent Information
- Application Number
- CN202411436367.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-18
AI Technical Summary
The existing serum amyloid A sensor is complex in operation, expensive, large in size and long in detection, so it is impossible to achieve wearable detection.
Using flexible fiber-based organic phototransistors, sensitive and efficient are prepared by using conductive polymer fibers and inorganic quantum dot conductive fibers as sources, drains and gates, and modifying serum amyloid A antibodies, combining gel electrolyte assembly. Serum amyloid A sensor.
It realizes rapid and sensitive detection of serum amyloid A, with specificity and short response time, and is suitable for wearable biosensors, with simple process, good flexibility and low toxicity.
Smart Images

Figure CN119486444A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectric sensing and biosensing technology, and in particular to a flexible fiber-based organic phototransistor serum amyloid A sensor and a preparation method thereof. Background Art
[0002] SAA is an α-globulin belonging to the apolipoprotein family. It weighs about 12kDa and its gene is expressed on chromosome 11. The serum content of SAA in normal people is <10mg / L. When the body is injured or infected, the SAA content can rapidly increase by about 1000 times within 4-6 hours, and then rapidly decrease to normal levels after the body clears the antigen. SAA has attracted attention from the research community as an efficient, specific and sensitive biomarker for swine flu detection. The secretion concentration of SAA in healthy human serum samples is 12.2±15.0μg·mL -1 , while during the swine flu infection period, the concentration of SAA will increase to 49.4±14.1μg·mL -1 As a new detection index, SAA is receiving more and more attention. Therefore, monitoring the SAA content in human serum is very important for controlling the body's inflammatory response, and it is very necessary to establish a new method for sensitive and rapid detection of SAA in human serum.
[0003] Phototransistor biosensors are phototransistor devices that convert light signals into electrical signals and are widely used in electronics, communications, military and medical fields. With the rapid development of science and technology, people's needs are constantly increasing, and the requirements for flexible phototransistor biosensors are also gradually increasing. Flexible substrates are receiving more and more attention because of their softness, lightness and low cost. Preparing high-performance photoelectric devices on flexible substrates and making the sensing of biological substances more sensitive has become one of the hot research topics.
[0004] A sensor that fixes biological components (enzymes, antigens, antibodies, DNA, etc.) or cells and tissues on a carrier as a sensitive element is called a biosensor.
[0005] Existing serum amyloid A sensor tests are complex to operate, expensive, large in size, and the detection method is time-consuming and labor-intensive, which cannot meet the requirements of wearable detection. Summary of the invention
[0006] In view of the defects of the above-mentioned prior art, the purpose of the present invention is to provide a flexible fiber-based organic phototransistor serum amyloid A sensor and a preparation method thereof. The preparation method uses two flexible fibers as substrates, immerses one fiber substrate in a dispersed mixed solution of a conductive polymer and an inorganic nano-oxide to obtain a conductive polymer fiber as the source and drain of the phototransistor; the other is a conductive fiber, on the surface of which uniform inorganic oxide nanorods are grown and inorganic quantum dots are adsorbed, which serves as the gate of the phototransistor; the gate is modified with a silane coupling agent, a serum amyloid A antibody (anti-SAA) solution and a biocompatible solution, and then the source and drain, the gate and an ion gel electrolyte are assembled to obtain a fiber-based organic phototransistor serum amyloid A sensor.
[0007] To achieve the above object, the present invention provides a method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor, comprising the following steps:
[0008] S1, preparing inorganic nano-oxide powder, dispersing the prepared inorganic nano-oxide powder into a conductive polymer solution and uniformly dispersing the powder by ultrasonication to obtain a mixed solution; the ratio of the conductive polymer solution to the inorganic nano-oxide in the mixed solution is 5-15 mL: 0.5-1.5 mg;
[0009] S2, immersing the fiber substrate in the mixed solution obtained in step S1 repeatedly n times to obtain a conductive polymer fiber adsorbed with n layers of conductive polymer and inorganic nano-oxide;
[0010] S3, preparing a conductive fiber with inorganic oxide nanorods grown on the surface; immersing the prepared inorganic oxide nanorod conductive fiber in a prepared inorganic quantum dot solution to obtain an inorganic quantum dot conductive fiber loaded with inorganic quantum dots and inorganic oxide nanorods;
[0011] S4, applying conductive silver paste to both ends of the conductive polymer fiber obtained in step S2 as source and drain electrodes, using the inorganic quantum dot conductive fiber obtained in step S3 as a gate electrode, and then fixing the fiber on a PET plastic plate and assembling it with a gel electrolyte to obtain a flexible fiber-based organic phototransistor;
[0012] S5, sequentially modifying the gate surface with a silane coupling agent, a serum amyloid A antibody solution, and a blocking solution to modify the inorganic quantum dot conductive fiber to obtain a flexible fiber-based organic phototransistor serum amyloid A sensor.
[0013] In the embodiments of the present application, the synergistic effect between conductive polymers and inorganic nano-oxides is utilized to improve the composite properties of the material and the biosensing effect of the device. At the same time, inorganic oxide nanorods are utilized to control the adsorption effect of inorganic quantum dots, thereby improving the photosensitivity and sensing performance of the device. Ultimately, a flexible fiber-based organic phototransistor serum amyloid A sensor with excellent comprehensive performance is obtained.
[0014] The flexible fiber-based organic phototransistor serum amyloid A sensor of the present invention has a simple preparation process, good flexibility, low toxicity, fast electrochemical response to serum amyloid A, good sensitivity, specificity for serum amyloid A detection, short response time, etc., and has great application potential in the field of wearable organic phototransistor biosensors.
[0015] In some embodiments, in step S1, the concentration of the conductive polymer in the mixed solution is 1.0 wt% to 1.3 wt%, and the concentration of the inorganic nano-oxide is 0.1 to 0.3 wt%; the conductive polymer is any one of PEDOT:PSS, polythiophene, and polyacetylene, preferably PEDOT:PSS.
[0016] In some embodiments, in step S3, the concentration of the inorganic quantum dot solution is 0.01 wt% to 0.1 wt%; the inorganic substance in the inorganic quantum dot solution is ZnO, SnO2 or C. Preferably, it is carbon quantum dots (CQDs).
[0017] In some embodiments, in step S1, the particle diameter of the inorganic nano-oxide is 100-200 nm; the inorganic nano-oxide is TiO2 or ZrO2, preferably TiO2.
[0018] In some embodiments, in step S3, the preparation method of the conductive fiber with inorganic oxide nanorods grown on the surface is: growing inorganic oxide nanorods on the fiber surface by a high-temperature hydrothermal method; the fiber substrate is carbon fiber or metal fiber, preferably carbon fiber.
[0019] In some embodiments, in step S3, the diameter of the inorganic oxide nanorods is 500-800 nm; the inorganic oxide nanorods are TiO2 or ZnO, preferably TiO2 nanorods.
[0020] In some embodiments, in step S2, the fiber substrate is immersed in the mixed solution for 5 to 20 minutes each time; and the number of layers n of the conductive polymer adsorbed on the conductive polymer fiber is 1 to 10 layers.
[0021] In some embodiments, in step S2, the fiber substrate is a fiber bundle composed of one or more of aramid fiber, nylon fiber, polyester fiber, cotton fiber, nylon fiber, and silk fiber, preferably cotton fiber.
[0022] In some embodiments, in step S5, the blocking solution is any one of bovine serum albumin, serum, and skimmed milk powder; preferably bovine serum albumin (BSA).
[0023] The silane coupling agent is any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and diethylenetriaminopropyltrimethoxysilane, preferably 3-aminopropyltriethoxysilane (APTES). The concentration of the silane coupling agent is 2%-2.5%.
[0024] To achieve the above objectives, the present invention also provides a flexible fiber-based organic phototransistor serum amyloid A sensor, which is prepared by the preparation method described in any of the technical solutions mentioned above.
[0025] The structure of the flexible fiber-based organic phototransistor serum amyloid A sensor is as follows: a conductive polymer fiber coated with conductive silver paste at both ends serves as a source and a drain, and an inorganic quantum dot conductive fiber modified with a serum amyloid A antibody solution serves as a gate; the source and drain electrodes and the gate are arranged in parallel with an interval of 1 to 2 mm, a gel electrolyte is provided at the interval between the two as an insulating layer, and the gel electrolyte completely covers the source and drain electrodes and the gate fiber; the conductive polymer fiber constitutes a channel between the source and drain electrodes.
[0026] The beneficial effects of the present invention are:
[0027] 1. The preparation method of the flexible fiber-based organic phototransistor serum amyloid A sensor provided by the present invention uses the fiber of composite conductive polymer and inorganic nano-oxide as the source and drain of the flexible electrochemical transistor, and uses the inorganic quantum dot conductive fiber as the gate and modifies the serum amyloid A antibody solution. The present invention uses the synergistic effect between the conductive polymer and the inorganic nano-oxide to increase the transmission efficiency of the channel electrons, so as to improve the composite performance of the material and the biosensing effect of the device; at the same time, the inorganic oxide nanorods are used to control the adsorption effect of the inorganic quantum dots, and the synergistic photoelectric effect of the nanomaterials and quantum dots is used to increase the transfer rate of the electrons, thereby improving the photosensitivity and sensing performance of the device, and significantly improving the electrochemical response of the electrode to serum amyloid A, and finally obtaining a flexible fiber-based organic phototransistor serum amyloid A sensor with excellent comprehensive performance.
[0028] 2. The flexible fiber-based organic phototransistor serum amyloid A sensor of the present invention has a simple preparation process, good flexibility, low toxicity, fast electrochemical response to serum amyloid A, good sensitivity, good reproducibility, high sensitivity, can be used for SAA detection in blood, has specificity for serum amyloid A detection, short response time, etc.
[0029] 3. The present invention prepares the material of the organic electrochemical transistor by liquid-phase immersion of the fiber substrate, which is beneficial to improving the dispersibility of the conductive polymer material and enhancing the amplification and transfer transconductance functions of the transistor; and the transistor is antibody-modified to obtain a serum amyloid A sensor with good flexibility and excellent performance.
[0030] 4. The flexible fiber-based organic phototransistor serum amyloid A sensor of the present invention uses flexible fibers as a substrate, has low toxicity, and can be used for sensing in the wearable field. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the cotton fiber in the flexible fiber-based organic electrochemical transistor in Example 1 of the present invention after being immersed in the mixed solution twice.
[0032] Figure 2 This is a scanning electron microscope image of the TiO2 nanopowder prepared in Example 1.
[0033] Figure 3 This is a scanning electron microscope image of TiO2 nanorods grown on carbon fiber in Example 1.
[0034] Figure 4 This is a scanning electron microscope image of the carbon fiber on which TiO2 nanorods were grown in Example 1 and immersed twice in the carbon quantum dot solution.
[0035] Figure 5 This is a graph showing the output characteristics of the fiber-based organic phototransistor prepared in Example 1 when no light is applied.
[0036] Figure 6 This is a transfer-transconductance characteristic curve of the fiber-based organic phototransistor prepared in Example 1 when no light is applied.
[0037] Figure 7 This is a comparison of the current changes when the same concentration of serum amyloid A is added with and without light.
[0038] Figure 8 This is a graph showing the sensing characteristics of serum amyloid A of the fiber-based organic phototransistor serum amyloid A sensor prepared in Example 1. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0040] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0041] The present invention provides a method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor, comprising the following steps:
[0042] S1, preparing inorganic nano-oxide powder, dispersing the prepared inorganic nano-oxide powder into a conductive polymer solution and uniformly dispersing the powder by ultrasonication to obtain a mixed solution; the ratio of the conductive polymer solution to the inorganic nano-oxide in the mixed solution is 5-15 mL: 0.5-1.5 mg;
[0043] The concentration of the conductive polymer in the mixed solution is 1.0 wt% to 1.3 wt%, and the concentration of the inorganic nano-oxide is 0.1 to 0.3 wt%.
[0044] The conductive polymer is any one of PEDOT:PSS, polythiophene and polyacetylene, preferably PEDOT:PSS, which has high conductivity, high compatibility with fibers, is easy to combine with fiber substrates, and can promote the compounding of inorganic nano-oxides on the surface of fiber substrates.
[0045] The particle diameter of the inorganic nano-oxide is 100-200 nm; the inorganic nano-oxide is TiO2 or ZrO2, preferably titanium dioxide, which can increase the channel electron mobility after being compounded on the surface of the fiber substrate.
[0046] The ice bath conditions for ultrasonic dispersion are 0-10°C, the ultrasonic time is 10-30min, and the power is 200-300W.
[0047] By controlling the concentration of the conductive polymer and the inorganic nano-oxide in the mixed solution and the ratio of the two, the bonding strength between the conductive polymer and the fiber substrate and the uniformity of the dispersion of the inorganic nano-oxide on the surface of the fiber substrate can be improved.
[0048] S2, immersing the fiber substrate in the mixed solution obtained in step S1 repeatedly n times to obtain a conductive polymer fiber adsorbed with n layers of conductive polymer and inorganic nano-oxide;
[0049] Specifically, the fiber substrate is a fiber bundle composed of one or more of aramid fiber, nylon fiber, polyester fiber, cotton fiber, nylon fiber, and silk fiber.
[0050] The fiber substrate is immersed in the mixed solution for 5 to 20 minutes each time; the number of layers n of the conductive polymer adsorbed on the conductive polymer fiber is 1 to 10 layers.
[0051] S3, preparing conductive fibers with inorganic oxide nanorods grown on the surface;
[0052] Immersing the prepared inorganic oxide nanorod conductive fiber in a prepared inorganic quantum dot solution to obtain an inorganic quantum dot conductive fiber loaded with inorganic quantum dots and inorganic oxide nanorods;
[0053] Specifically, the preparation method of the conductive fiber with inorganic oxide nanorods grown on the surface is: growing inorganic oxide nanorods on the fiber surface by a high-temperature hydrothermal method;
[0054] The fiber substrate is carbon fiber or metal fiber.
[0055] The diameter of the inorganic oxide nanorods is 500 to 800 nm.
[0056] The inorganic oxide nanorods are TiO2 or ZnO, preferably titanium dioxide nanorods, which have small particles and are evenly distributed, and after growing on the fiber substrate, the fiber substrate has a higher specific surface area.
[0057] The inorganic substance in the inorganic quantum dot solution is ZnO, SnO2 or C. Carbon quantum dots (CQDs) are preferred, as they are extremely small particles that can be easily attached to the surface and gaps of titanium dioxide nanorods, increasing the binding sites of bioactive substances (SAA antibodies); moreover, the nanomaterials are evenly distributed on the surface of the fiber substrate, which is beneficial to improving the mobility of electrons and the response of transistor devices.
[0058] The concentration of the inorganic quantum dot solution is 0.01wt% to 0.1wt%.
[0059] By controlling the concentration of the inorganic oxide quantum dot solution, the loading amount of the inorganic oxide quantum dots on the surface of the inorganic oxide nanorods is controlled so that they cooperate with the nanorods, and the phototransistor finally prepared has both light absorption and conductivity properties.
[0060] S4, applying conductive silver paste to both ends of the conductive polymer fiber obtained in step S2 as source and drain electrodes, using the inorganic quantum dot conductive fiber obtained in step S3 as a gate electrode, and then fixing the fiber on a PET plastic plate and assembling it with a gel electrolyte to obtain a flexible fiber-based organic phototransistor;
[0061] S5, sequentially modifying the gate surface with a silane coupling agent, a serum amyloid A antibody solution, and a blocking solution to modify the inorganic quantum dot conductive fiber to obtain a flexible fiber-based organic phototransistor serum amyloid A sensor.
[0062] Specifically, the SAA antibody is dripped on the gate of the organic electrochemical transistor, placed in a refrigerator to dry, and then the dripping is repeated 3 to 5 times after a period of time, so that the SAA antibody is firmly attached to the gate. The transistor device treated with the SAA antibody is used to detect SAA, and its performance is excellent and repeatable.
[0063] The serum amyloid A antibody solution is prepared by serum amyloid A antibody (anti-SAA), 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC), and N-hydroxysuccinimide (NHS). The executable concentration ratio of EDC: NHS: anti-SAA is 1.2:1.2:2.2.
[0064] The blocking solution is any one of bovine serum albumin, serum, and skimmed milk powder;
[0065] The silane coupling agent is any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and diethylenetriaminopropyltrimethoxysilane; the concentration of the silane coupling agent is 2%-2.5%.
[0066] The present invention also provides a flexible fiber-based organic phototransistor serum amyloid A sensor, which is prepared by the above-mentioned preparation method;
[0067] The structure of the flexible fiber-based organic phototransistor serum amyloid A sensor is as follows: a conductive polymer fiber coated with conductive silver paste at both ends serves as the source and drain electrodes, and an inorganic quantum dot conductive fiber modified with a serum amyloid A antibody solution serves as the gate electrode; the source, drain and gate electrodes are arranged in parallel with an interval of 1 to 2 mm, and a gel electrolyte is provided at the interval between the two electrodes as an insulating layer, and the gel electrolyte completely covers the source, drain and gate fibers; the conductive polymer fiber constitutes a channel between the source and drain electrodes.
[0068] This flexible fiber-based organic phototransistor serum amyloid A sensor can be used to detect the content of SAA in human serum.
[0069] In the embodiments of the present application, the synergistic effect of inorganic nano-oxides and conductive polymers is utilized to increase the transmission efficiency of channel electrons, and the synergistic photoelectric effect of nanomaterials and quantum dots is utilized to increase the electron transfer rate, thereby significantly improving the electrochemical response of the electrode to serum amyloid A.
[0070] The preparation method of the flexible fiber-based organic phototransistor serum amyloid A sensor provided by the present invention is described below with reference to specific examples.
[0071] Example 1
[0072] This embodiment provides a method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor, comprising the following steps:
[0073] S1, preparation of nano titanium dioxide powder:
[0074] Prepare 0.1M ammonium hexafluorotitanate [(NH4)2TiF6] solution and 0.3M boric acid (H3BO3) solution respectively, mix the two, add a small amount of anatase nano titanium dioxide to the mixed solution, and react in a water bath at 35°C for 12 hours. Filter, wash and dry the powder precipitated in the solution, and then heat it to 300°C in a muffle furnace at a rate of 5°C / min and calcine it for 2 hours to obtain nano titanium dioxide powder, such as Figure 2 As shown, the particle size of nano titanium dioxide is 150-200nm.
[0075] Prepare PEDOT:PSS solution:
[0076] 20 mL of PEDOT:PSS was added to a 50 mL beaker, and then 0.2 mL of dimethyl sulfoxide (DMSO) and 1 mL of ethylene glycol were added, and the mixture was dispersed evenly by ultrasonication to prepare a PEDOT:PSS solution.
[0077] 1.5 mg of nano-titanium dioxide was dispersed in 15 mL of PEDOT:PSS solution, and ultrasonication was used to make the dispersion uniform, thereby preparing a conductive polymer mixed solution;
[0078] S2, cleaning the stains on the surface of the cotton fiber substrate: the cotton fiber is placed in deionized water and anhydrous ethanol for ultrasonic cleaning for 15 minutes, and then stored for later use;
[0079] The cleaned cotton fiber substrate is immersed in the mixed solution of step S1 twice, each time for 15 minutes, to obtain a composite conductive polymer cotton fiber adsorbing two layers of conductive polymer;
[0080] S3, Growth of TiO2 nanorods on carbon fibers:
[0081] The carbon fiber was placed in deionized water and anhydrous ethanol for ultrasonic cleaning for 15 min, and then stored for later use;
[0082] First, prepare 60 mL of 6M hydrochloric acid solution for later use, add 1 mL of tetrabutyl titanate, stir and mix the solution, transfer it to 100 mL of polytetrafluoroethylene liner, put the treated carbon fiber in, and heat the reaction at 150°C for 10 hours.
[0083] After the reaction, the carbon fiber was cleaned with deionized water, dried, and then heated to 500°C in a muffle furnace at a rate of 5°C / min for 2h to obtain titanium dioxide nanorod-carbon fiber. Figure 3 As shown, the diameter of the titanium dioxide nanorods is 500 to 800 nm.
[0084] Preparation of carbon quantum dot solution: Take the same mass of urea and p-phenylenediamine respectively and add them into 30 mL of ultrapure water, mix and stir evenly, then transfer the solution to 100 mL of polytetrafluoroethylene liner, heat and react at 160°C for 10 hours, and after the reaction, cool the solution to room temperature to obtain a brown transparent carbon quantum dot solution.
[0085] The obtained titanium dioxide nanorod-carbon fiber was immersed in the prepared inorganic quantum dot solution twice, with each immersion time being 15 minutes, to obtain carbon quantum dot-titanium dioxide nanorod-conductive fiber.
[0086] S4, Fabrication of flexible fiber-based organic electrochemical transistors:
[0087] Take a composite conductive polymer cotton fiber prepared in step S2, apply conductive silver paste on both ends as source and drain electrodes, take a carbon quantum dot-titanium dioxide nanorod-carbon fiber prepared in step S3, both of which are about 2 cm in length, and place them in parallel on a PET plastic plate with a spacing of 0.1 mm, then drip an ion gel electrolyte so that the electrolyte covers the two fibers, thereby obtaining a flexible fiber-based organic electrochemical transistor.
[0088] S5, prepare serum amyloid A antibody solution: first use an electronic balance to weigh 1.9g of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) powder, the solvent is deionized water, and prepare it into a 0.4M solution. Then weigh 0.345g of N-hydroxysuccinimide (NHS), the solvent is deionized water, and prepare it into a 0.5M solution. Then take a certain amount of SAA antibody, the solvent is PBS buffer, and prepare it into a 50μg / mL solution. The feasible concentration ratio of EDC: NHS: SAA antibody is 1.2:1.2:2.2, and the mixed solution is placed in a microcentrifuge tube to activate the -COOH group in the SAA antibody. The prepared SAA antibody solution is placed in a refrigerator at 4°C for storage.
[0089] 3-Aminopropyltriethoxysilane (APTES), serum amyloid A antibody (anti-SAA) solution, and bovine serum albumin (BSA) are sequentially added to the gate of the transistor device obtained in step S4 to prepare a flexible fiber-based organic phototransistor serum amyloid A sensor.
[0090] See also Figure 1 As shown, Figure 1 This is a scanning electron microscope image of the cotton fiber after being washed in Example 1 and immersed in the mixed solution twice. It can be seen from the figure that after being immersed in the mixed solution of PEDOT:PSS and TiO2, the surface of the cotton fiber is now wrapped with a uniformly dispersed conductive polymer, and the gaps between the fibers are also covered with the conductive polymer.
[0091] See also Figure 4 As shown, Figure 4 This is a scanning electron microscope image of the carbon fiber after the TiO2 nanorods were grown in Example 1 and immersed in the carbon quantum dot solution twice. It can be seen from the figure that the surface of the TiO2 nanorods, which originally had a clear structure, became blurred after being immersed in the carbon quantum dot solution twice, indicating that the carbon quantum dots have been distributed and covered on the surface of the TiO2 nanorods.
[0092] See also Figures 5-6 As shown, Figure 5 The output characteristic curve of the fiber-based organic phototransistor prepared in Example 1 without light is shown in the figure. It can be seen from the figure that the curve is a typical depletion mode, that is, when the gate voltage is constant, as the source-drain voltage increases, the output current gradually increases, and the curve shows a good linear trend. When the source-drain voltage is constant, as the gate voltage increases, the output current gradually decreases, indicating that the prepared cotton fiber-based organic phototransistor has a good working state.
[0093] Figure 6 This is a transfer-transconductance characteristic curve of the cotton fiber-based organic phototransistor prepared in Example 1 when no light is applied. It can be seen from the figure that when the source-drain voltage is constant, as the gate voltage increases, the current between the source and the drain gradually decreases, which is consistent with the working principle of the transistor. Figure 5 The output curve is consistent.
[0094] Serum amyloid A (SAA) solutions of different concentrations were prepared, 1 mg SAA was weighed and dissolved in 100 ml PBS buffer solution at pH = 7.2 to obtain a 10 mg / L SAA solution, and then the 10 mg / L SAA solution was diluted with PBS buffer solution at pH = 7.2 in a certain proportion to obtain SAA solutions with concentrations of 1 mg / L, 100 μg / L, 10 μg / L, 1 μg / L, and 100 ng / L.
[0095] Figure 7 This is a comparison of the current changes when the same concentration of serum amyloid A is added with and without light. As can be seen from the figure, under light conditions, the current change when 100ng / L of SAA is added is greater than the current change when no light is added. This is because the materials on the transistor gate, titanium dioxide nanorods and carbon quantum dots, are photosensitive materials that have a certain response to light.
[0096] Figure 8The graph is a sensing characteristic curve of serum amyloid A of the fiber-based organic phototransistor serum amyloid A sensor prepared in Example 1. As can be seen from the figure, the SAA sensor prepared by the present invention has a step-type current response to different concentrations of SAA, indicating that the sensor can sensitively detect SAA.
[0097] Comparative Example 1
[0098] Comparative Example 1 provides a method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor. Compared with Example 1, the difference is that in step S1, no inorganic nano oxide powder is added, in step S2, the cotton fiber is immersed in the prepared PEDOT:PSS solution, and in step S4, a cotton fiber treated by the aforementioned immersion is taken as an electrode. Specifically, the cotton fiber soaked only in the PEDOT:PSS solution is used as the source and drain to prepare an organic phototransistor device. The rest is roughly the same as Example 1 and will not be repeated here.
[0099] Comparative Example 2
[0100] Comparative Example 2 provides a method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor. Compared with Example 1, the difference is that in step S3, inorganic oxide nanorods are not grown on the surface of the conductive fiber, but the conductive fiber is directly immersed in the configured inorganic quantum dot solution. The rest is roughly the same as Example 1 and will not be repeated here.
[0101] Comparative Example 3
[0102] Comparative Example 3 provides a method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor. Compared with Example 1, the difference is that: no inorganic quantum dot solution is used, and in step S3, the titanium dioxide nanorod-carbon fiber is not immersed in the inorganic quantum dot solution; specifically, in step S3, the prepared titanium dioxide nanorod-carbon fiber is directly used as the gate of the transistor, and the rest is roughly the same as Example 1, which will not be repeated here.
[0103] The electrical performance indicators of the flexible fiber-based organic phototransistors of Example 1 and Comparative Examples 1 to 3 were tested, and the results are shown in the following table.
[0104] <![CDATA[Gate voltage V g (V)]]> <![CDATA[I ph (mA)]]> <![CDATA[Source-drain current ΔI ds (mA)]]> Example 1 -0.8 0.54 2.29 Comparative Example 1 -0.8 0.23 1.35 Comparative Example 2 -0.8 0.19 2.13 Comparative Example 3 -0.8 0.25 2.25
[0105] According to the above table, by comparing Example 1 with Comparative Example 1, it can be seen that the current of the organic phototransistor prepared in Comparative Example 1 is smaller than that of the transistor in Example 1.
[0106] The reason is: the addition of nano-titanium dioxide can form a heterojunction with PEDOT:PSS, which will generate more electron-hole pairs when voltage is applied, thereby improving electron mobility. However, when cotton fibers only soaked in PEDOT:PSS solution are used as the source and drain of the transistor, no nano-titanium dioxide is added, that is, there is no composite effect of conductive polymer and inorganic nano-oxide, so the current is reduced.
[0107] Comparing Example 1 with Comparative Example 2, it can be seen that the photocurrent of the organic phototransistor prepared in Comparative Example 2 is smaller than that of the transistor in Example 1.
[0108] The reason is: titanium dioxide nanorods are a photosensitive material that responds to light. Since titanium dioxide nanorods are not grown, the amount of carbon quantum dots adsorbed by the fiber is reduced, and no heterojunction is formed with the titanium dioxide nanorods. Only the fiber soaked in carbon quantum dots is used as the gate, resulting in a decrease in the photocurrent of the transistor.
[0109] Comparing Example 1 with Comparative Example 3, it can be seen that the photocurrent of the organic phototransistor prepared in Comparative Example 3 is smaller than that of the transistor in Example 1.
[0110] The reason is: titanium dioxide nanorods and quantum dot solution can form a heterojunction, which enhances the response to light. However, the prepared titanium dioxide nanorod-carbon fiber is not immersed in an inorganic quantum dot solution, and only the carbon fiber attached with the nanorods is used as the gate. Since no photosensitive carbon quantum dots are added, the photocurrent of the transistor decreases.
[0111] Examples 2-3 and Comparative Examples 4-5
[0112] The main difference between Examples 2-3 and Comparative Examples 4-5 and Example 1 is that in step S1, the ratio of the conductive polymer solution to the inorganic nano-oxide in the mixed solution is different, as shown in the following table. The rest is roughly the same as Example 1 and will not be repeated here.
[0113]
[0114] The fiber-based organic phototransistors of Examples 1 to 3 and Comparative Examples 4 to 5 were tested for electrical performance indicators, and the results are shown in the following table.
[0115] <![CDATA[Gate voltage V g (V)]]> <![CDATA[I ph (mA)]]> <![CDATA[Source-drain current ΔI ds (mA)]]> <![CDATA[Transconductance g m (mS)]]> Example 1 -0.8 0.54 2.29 22.94 Example 2 -0.8 0.53 2.25 22.32 Example 3 -0.8 0.55 2.26 22.61 Comparative Example 4 -0.8 0.54 0.09 9.89 Comparative Example 5 -0.8 0.52 0.06 6.24
[0116] By comparing Examples 1-3 and Comparative Examples 4-5, it can be seen that when the content of nano-titanium dioxide and the amount of PEDOT:PSS solution used are controlled within a certain range, the current and transconductance of the fiber-based transistor are maximized, and the current regulation effect is good; when the content of nano-titanium dioxide is too much, since titanium dioxide is not conductive, the conductivity of the entire polymer fiber is reduced and the current is reduced; when the content of nano-titanium dioxide is too little, the degree of compositeness between it and the conductive polymer PEDOT:PSS is reduced, which weakens the synergistic effect and leads to a decrease in current.
[0117] Examples 4-5 and Comparative Examples 6-7
[0118] The main difference between Examples 4-5 and Comparative Examples 6-7 and Example 1 is that in step S3, the concentration of the inorganic quantum dot solution is different, as shown in the following table. The rest is substantially the same as Example 1 and will not be repeated here.
[0119] Concentration of inorganic quantum dot solution Example 1 0.08wt% Example 4 0.01wt% Example 5 0.1wt% Comparative Example 6 0.005wt% Comparative Example 7 0.5wt%
[0120] The fiber-based organic phototransistors of Examples 1, 4-5 and Comparative Examples 6-7 were tested for electrical performance indicators, and the results are shown in the following table.
[0121]
[0122] By comparing Examples 1, 4-5 and Comparative Examples 6-7, it can be seen that when the concentration of the inorganic quantum dot solution is within a reasonable range, the photocurrent of the transistor does not change significantly, and the source-drain current will slightly decrease due to the increase in concentration. This is because excessive concentration will lead to increased resistance. When the concentration of quantum dots is too small or too large, the photocurrent of the transistor will decrease. This is because as the concentration of quantum dots decreases, the response of the gate to light will weaken accordingly. When the concentration of quantum dots is too large, their adsorption on the gate surface will be uneven, resulting in a decrease in photocurrent.
[0123] Examples 6-8 and Comparative Example 8
[0124] The main difference between Examples 6-8 and Comparative Example 8 and Example 1 is that the conductive polymer PEDOT:PSS is replaced with polyaniline, polythiophene, polyacetylene, and polypyrrole, as shown in the following table. The rest is substantially the same as Example 1 and will not be described again.
[0125]
[0126]
[0127] The fiber-based organic phototransistors of Examples 1, 6-8 and Comparative Example 8 were tested for electrical performance indicators, and the results are shown in the following table.
[0128]
[0129] It can be seen from the above table that after replacing the conductive polymer PEDOT:PSS with polyaniline, polythiophene and polyacetylene, the electrical properties of the prepared fiber-based organic electrochemical transistors are not much different and are similar, so it is believed that polyaniline, polythiophene and polyacetylene can be used as conductive high molecular polymer materials of this invention.
[0130] Comparing Example 1 with Comparative Example 8, it can be seen that the current of the organic phototransistor prepared in Comparative Example 8 is smaller than that of the transistor in Example 1. The reason is that the band gap of polypyrrole is larger than that of PEDOT:PSS, and the electron affinity is also larger. The growth morphology of polypyrrole is not conducive to the uniform dispersion of TiO2, so the current is significantly reduced. Therefore, the performance of the phototransistor prepared by polypyrrole is poor.
[0131] Examples 9-13
[0132] Examples 9-13 provide a method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor. Compared with Example 1, the difference is that the fiber substrate cotton fiber is replaced by aramid fiber, nylon fiber, polyester fiber, nylon fiber, or silk fiber.
[0133] Experiments show that by replacing the fiber substrate with aramid fiber, nylon fiber, polyester fiber, polyamide fiber, and silk fiber, the resulting flexible fiber-based organic phototransistor serum amyloid A sensor also has sensitive detection of serum amyloid A and can be used as a feasible fiber substrate.
[0134] Comparative Example 9
[0135] This comparative example provides a method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor. Compared with Example 1, the difference is that in step S5, when modifying the transistor gate, 3-aminopropyltriethoxysilane (APTES) is not added. The rest is roughly the same as Example 1 and will not be repeated here.
[0136] Comparative Example 10
[0137] This comparative example provides a flexible fiber-based organic phototransistor serum amyloid A sensor and a preparation method thereof. Compared with Example 1, the difference is that in step S5, when preparing the serum amyloid A antibody solution, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are not added, and the rest is roughly the same as Example 1 and will not be repeated here.
[0138] Comparative Example 11
[0139] This comparative example provides a flexible fiber-based organic phototransistor serum amyloid A sensor and a preparation method thereof. Compared with Example 1, the difference is that in step S5, when modifying the transistor gate, bovine serum albumin (BSA) is not added, and the rest is roughly the same as Example 1 and will not be repeated here.
[0140] The fiber-based organic phototransistor sensors of Example 1 and Comparative Examples 9-11 were tested for sensing performance indicators, and the results are shown in the following table.
[0141] SAA concentration (mg / L) <![CDATA[ΔI ds (mA)]]> Example 1 1 2.29 Comparative Example 9 1 0.05 Comparative Example 10 1 0.08 Comparative Example 11 1 0.09
[0142] As can be seen from the above table, by comparing Example 1 with Comparative Example 9, 3-aminopropyltriethoxysilane (APTES) was not added in Comparative Example 9. Since the function of the silane coupling agent is to fix the antibody, the amount of SAA antibody fixed on the gate surface is reduced after the lack of APTES, and the binding sites on the gate surface are reduced, so the sensing current is reduced when the SAA antigen is added.
[0143] In Comparative Example 10, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) were not added when preparing the SAA antibody solution. The function of these two amino compounds is to make the SAA antibody combine with the amino group and further fix it on the gate surface. Failure to add these two substances will lead to a decrease in the amount of SAA antibody fixed and thus a decrease in the sensing current.
[0144] In Comparative Example 11, bovine serum albumin (BSA) was not added. The function of this blocking solution is to block the non-binding sites on the gate surface. The lack of this substance will cause the SAA antigen to bind to other impurity proteins when the SAA antigen is added, thereby resulting in a decrease in the sensing current.
[0145] In summary, the present invention provides a method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor, using composite conductive polymer and inorganic nano-oxide fibers as the source and drain of the flexible electrochemical transistor, and inorganic quantum dot-conductive fibers and fibers modified with serum amyloid A antibody solution as the gate; the synergistic effect between the conductive polymer and the inorganic nano-oxide is used to improve the composite performance of the material and the biosensing effect of the device, and the inorganic oxide nanorods are used to control the adsorption effect of the inorganic quantum dots, thereby improving the photosensitivity and sensing performance of the device, and finally obtaining a flexible fiber-based organic phototransistor serum amyloid A sensor with excellent comprehensive performance. The flexible fiber-based organic phototransistor serum amyloid A sensor of the present invention has a simple preparation process, good flexibility, low toxicity, fast electrochemical response to serum amyloid A, good sensitivity, specificity for serum amyloid A detection, short response time, etc., and has great application potential in the field of wearable organic phototransistor biosensors.
[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a flexible fiber-based organic phototransistor serum amyloid A sensor, characterized in that: The following steps are involved: S1, preparing inorganic nano-oxide powder, dispersing the prepared inorganic nano-oxide powder into a conductive polymer solution and uniformly dispersing the powder by ultrasonication to obtain a mixed solution; the ratio of the conductive polymer solution to the inorganic nano-oxide in the mixed solution is 5-15 mL: 0.5-1.5 mg; S2, immersing the fiber substrate in the mixed solution obtained in step S1 repeatedly n times to obtain a conductive polymer fiber adsorbed with n layers of conductive polymer and inorganic nano-oxide; S3, preparing a conductive fiber with inorganic oxide nanorods grown on the surface; immersing the prepared inorganic oxide nanorod conductive fiber in a prepared inorganic quantum dot solution to obtain an inorganic quantum dot conductive fiber loaded with inorganic quantum dots and inorganic oxide nanorods; S4, applying conductive silver paste to both ends of the conductive polymer fiber obtained in step S2 as source and drain electrodes, using the inorganic quantum dot conductive fiber obtained in step S3 as a gate electrode, and then fixing the fiber on a PET plastic plate and assembling it with a gel electrolyte to obtain a flexible fiber-based organic phototransistor; S5, sequentially modifying the gate surface with a silane coupling agent, a serum amyloid A antibody solution, and a blocking solution to modify the inorganic quantum dot conductive fiber to obtain a flexible fiber-based organic phototransistor serum amyloid A sensor.
2. The method for preparing the flexible fiber-based organic phototransistor serum amyloid A sensor according to claim 1, characterized in that: In step S1, the concentration of the conductive polymer in the mixed solution is 1.0 wt% to 1.3 wt%, and the concentration of the inorganic nano-oxide is 0.1 to 0.3 wt%; the conductive polymer is any one of PEDOT:PSS, polythiophene, and polyacetylene.
3. The method for preparing the flexible fiber-based organic phototransistor serum amyloid A sensor according to claim 1, characterized in that: In step S3, the concentration of the inorganic quantum dot solution is 0.01wt% to 0.1wt%; the inorganic substance in the inorganic quantum dot solution is ZnO, SnO2 or C.
4. The method for preparing the flexible fiber-based organic phototransistor serum amyloid A sensor according to claim 1, characterized in that: In step S1, the particle diameter of the inorganic nano-oxide is 100-200 nm; the inorganic nano-oxide is TiO2 or ZrO2.
5. The method for preparing the flexible fiber-based organic phototransistor serum amyloid A sensor according to claim 1, characterized in that: In step S3, the preparation method of the conductive fiber with inorganic oxide nanorods grown on the surface is: growing inorganic oxide nanorods on the fiber surface by a high-temperature hydrothermal method; the fiber substrate is carbon fiber or metal fiber.
6. The method for preparing the flexible fiber-based organic phototransistor serum amyloid A sensor according to claim 1, characterized in that: In step S3, the diameter of the inorganic oxide nanorods is 500-800 nm; the inorganic oxide nanorods are TiO2 or ZnO.
7. The method for preparing the flexible fiber-based organic phototransistor serum amyloid A sensor according to claim 1, characterized in that: In step S2, the fiber substrate is immersed in the mixed solution for 5 to 20 minutes each time; and the number of layers n of the conductive polymer adsorbed on the conductive polymer fiber is 1 to 10 layers.
8. The method for preparing the flexible fiber-based organic phototransistor serum amyloid A sensor according to claim 1, characterized in that: In step S2, the fiber base material is a fiber bundle composed of one or more of aramid fiber, nylon fiber, polyester fiber, cotton fiber, nylon fiber, and silk fiber.
9. The method for preparing the flexible fiber-based organic phototransistor serum amyloid A sensor according to claim 1, characterized in that: In step S5, the blocking solution is any one of bovine serum albumin, serum, and skimmed milk powder; the silane coupling agent is any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and diethylenetriaminepropyltrimethoxysilane; and the concentration of the silane coupling agent is 2%-2.5%.
10. A flexible fiber-based organic phototransistor serum amyloid A sensor, characterized in that: The flexible fiber-based organic phototransistor serum amyloid A sensor is prepared according to the preparation method according to any one of claims 1 to 9; The structure of the flexible fiber-based organic phototransistor serum amyloid A sensor is as follows: a conductive polymer fiber coated with conductive silver paste at both ends serves as a source and drain electrode, and an inorganic quantum dot conductive fiber modified with a serum amyloid A antibody solution serves as a gate electrode; the source and drain electrodes and the gate electrode are arranged in parallel with an interval of 1 to 2 mm, a gel electrolyte is provided at the interval between the two electrodes as an insulating layer, and the gel electrolyte completely covers the source and drain electrodes and the gate fiber; and the conductive polymer fiber constitutes a channel between the source and drain electrodes.